Use of treated wastewater for irrigation and its effects of soil and plant health under Natuurboerdery Farming System - Kgopa, Pholosho Mmateko (My University, 2020)
Due to high incidents of drought in the semi-arid regions of Limpopo Province, South Africa, the potential feasibility of using treated wastewater for irrigating vegetable crops had been researched and developed under the best practices of Natuurboerdery farming system. The investigation aimed at the development of soil and plant health management strategies for crops irrigated with treated wastewater that could ameliorate the ever-increasing demand for fresh irrigation water in the Province. Seven specific objectives, reduced to three overall objectives under Natuurboedery farming system were intended to investigate (1) the chemical and biological quality of treated wastewater used in irrigation with respect to disposal points and sampling period, (2) the responses of soil physico-chemical properties, heavy metal distribution and biological-soil-health indicators to irrigation with treated wastewater under field conditions and (3) the partitioning of cations and heavy metals in root, stem and leaf tissues of onion, tomato and a selected weed plant irrigated with treated wastewater. In each objective, unless otherwise stated, treatment effects were described at the probability level of 5%. In Objective 1, relative to the borehole water, treated wastewater had lower concentration of Ca, Mg, K, Na, Cl, HCO3 - , SO4 - , Zn, Cr and Pb, with temporal and spatial tendencies in accumulation of certain elements. In contrast, the treated wastewater had higher loads of pathogenic microbes that included bacteria (Escherichia coli, Salmonella spp., Shigella spp. and Vibrio spp.), protozoa (Entamoeba histolytica) and two helminths (Schistosoma mansoni; Ascaris lumbricoides), with temporal and spatial tendencies. In Objective 2, Al and Cr tended to be high in deeper soil layers (60-100 cm), whereas most essential nutrient elements and essential heavy metals (Cu, Fe, Mn, Ni, Zn, As, Cr and Pb) were contained in the upper soil levels (0-40 cm). The upper soil levels were also characterised by having substantial attributes of root health, namely, soil organic carbon, active carbon and potentially mineralisable nitrogen. In Objective 3, root, stem and leaf tissues of horseweed (Conyza canadensis L.), onion (Allium cepa L.) and tomato (Solanum lycopersicum L.) plants had different accumulation abilities for different metals, except for As. Contrary to the expectation, the onion bulb contained less test cations and heavy metals. In conclusion, in terms of chemical component at the time of sampling, as depicted from the water and soil samples, the treated wastewater was suitable for irrigation. However, in terms of pathogenic microbes, the treated wastewater was not suitable for irrigating crops intended for human consumption due to significantly higher loads than the permissible standards. Amongst all observed challenges, the reduction of pathogenic microbes should be given priority since it contravened existing national and international standards for using treated wastewater for in irrigation of crops intended for human consumption.
Thesis(Ph.D. Agriculture (Soil Science)) -- University of Limpopo, 2020
Keywords: Drought; Natuurboerdery; Chemical; Wastewater; Solanum Lycopersicum; Water reuse; Irrigation -- South Africa -- Limpopo; Plants -- Effect of graywater on; Water -- Purification